WEAVING STORIES: THE SCIENCE BEHIND THE STUDY OF THE MYGALOMORPHS OF ARGENTINA (Boletín de la Sociedad Zoológica del Uruguay, 2025)
Mygalomorph spiders (infraorder Mygalomorphae) are a group with a rich evolutionary history, a wide variety of life strategies and unique ecological adaptations, making them excellent study models. Since 2006, we have been studying mygalomorphs from different approaches, such as taxonomy, systematic, biogeography, behavior, ecology and natural history. This essay gathers the methodologies used in our researches, including specimens collection, field work, and the implementation of cladistic analysis based on morphological features, together with molecular tools for clarifying complex evolutionary relationships. We also studied reproductive biology, behavior and ecology, for a deeper and integrative understanding of the relationship between the mygalomorph and their environment. These advances not only enrich the knowledge about the group's biodiversity but also contribute to its conservation and the development of projections of known and unknown species.
Keywords: methodology; spider; integrative studies; study models